The Mediation Effect of Hyperarousal Symptoms on the Relationship Between Childhood Physical Abuse and Suicidal Ideation of Patients With PTSD - Kwon, Aeran; Lee, Hyun Seo; Lee, Seung-Hwan (Frontiers in Psychiatry, 2021)
Objective: This study examined the influence of childhood trauma, posttraumatic stress disorder (PTSD), and depression on suicide in patients with PTSD through path analysis. Materials and Methods: A total of 114 patients with PTSD (36 men and 78 women) were recruited and completed psychological assessments including the Childhood Trauma Questionnaire, the scale for suicidal ideation, the clinician-administered PTSD scale for the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, the PTSD checklist, and the Hospital Anxiety and Depression Scale. Structural equation modeling was used to evaluate the results. We developed a model including childhood traumatic experience as the causal variable, suicidal ideation as a result variable, and PTSD and depression as mediation variables. PTSD symptoms were divided into four clusters (intrusion, avoidance, altered cognitions and mood, and altered arousal and reactivity (hyperarousal)) to determine predictive power for suicide. Results: PTSD symptoms fully mediated the relationship between childhood physical abuse and suicidal ideation. Furthermore, PTSD symptoms fully mediated the relationship between childhood physical abuse and depression. Among the PTSD symptoms, hyperarousal was the only symptom cluster that mediated the relationship between childhood physical abuse and suicidal ideation. The symptom clusters of altered cognition and mood as well as hyperarousal mediated the relationship between childhood physical abuse and depression. Conclusions: This study found that the experience of childhood physical abuse had a long-lasting influence on the lives of patients with PTSD. These patients with experience of childhood physical abuse tend to suffer from hyperarousal and failure in neurophysiological regulation, which may lead them to develop suicidal behaviors as a means to end such adversities.